Visual strategies for co-design with a community partner - Fry, Aaron; Overby, Carol; Wilson, Jennifer (FormAkademisk, 2017)
Deficient financial literacy is an important international problem, and research suggests the potential effectiveness of narrative visualizations. This paper presents a case study: a collaboration between a class of design students and a community-based financial-counseling organization to develop financial-literacy comic strips for use with the organization’s low-income clients. We describe and examine the communication challenges between a community partner and an academic institution, detailing the several communication modes employed. These modes include questionnaire and surveys of the counsellors; emails directly between students and counsellors; and most successfully, a hands-on visualization workshop with counsellors. The visualizations engaged counsellors with generated (based) design practices, which resulted in superior communication with design students. Lessons from this experience may be broadly useful for any collaborative efforts among academic institutions, design students and community partners.